The first zoeal stage morphology of Crossotonotus spinipes (De Man, 1888) and Pseudopalicus serripes (Alcock & Anderson, 1895), with implications for Palicoid systematics (Crustacea: Brachyura: Palicoidea) - Clark, P.F. (2014)
Zootaxa